1988
DOI: 10.1002/j.1460-2075.1988.tb03195.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of replication of plasmid R1: kinetics of in vitro interaction between the antisense RNA, CopA, and its target, CopT.

Abstract: The frequency of replication of IncFII plasmids is regulated by the availability of a rate‐limiting protein, RepA. This protein acts to promote initiation of replication and its synthesis is negatively controlled both at the transcriptional and translational level. The translational control is exerted by the binding of a small antisense RNA, CopA RNA, to its target, CopT, which is located in the leader region of the RepA mRNA. As a consequence, formation of RepA is inhibited. Here we demonstrate the binding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
150
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 117 publications
(162 citation statements)
references
References 45 publications
10
150
2
Order By: Relevance
“…In naturally occurring antisense RNA-regulated systems, RNA secondary structures are known to influence the kinetics of double strand formation in vitro [35]. These measured differences are directly correlated with biological effectiveness in vivo [36][37][38][39]. A similar correlation between RNA-RNA annealing kinetics in vitro and efficacy in human cells has been observed for artificial Antisense RNAs directed against HIV-1 [40,41].…”
Section: Discussionmentioning
confidence: 70%
“…In naturally occurring antisense RNA-regulated systems, RNA secondary structures are known to influence the kinetics of double strand formation in vitro [35]. These measured differences are directly correlated with biological effectiveness in vivo [36][37][38][39]. A similar correlation between RNA-RNA annealing kinetics in vitro and efficacy in human cells has been observed for artificial Antisense RNAs directed against HIV-1 [40,41].…”
Section: Discussionmentioning
confidence: 70%
“…Interaction of such highly structured antisense RNA molecules with their targets is likely to involve several steps and starts with the formation of so-called kissing complexes between the singlestranded loops of antisense and target RNA. This concept was initially proposed by for the interaction of RNAI and RNAII of ColEl and was later supported by both in vivo and in vitro studies of the interaction of the CopA antisense RNA of plasmid R1 with its target CopT (31)(32)(33). In vitro experiments with the R1 system even suggested that formation of the kissing complex is sufficient for the inhibitory action of CopA to occur (43).…”
Section: Materlils and Methodsmentioning
confidence: 89%
“…Sok RNA and variants of truncated hok mRNA were synthesized in vitro, gelpurified, and renatured. Using an in vitro binding assay (38), the apparent secondorder binding-rate constants (K app ) of Sok RNA association with truncated wild-type and mutant hok mRNAs were determined (Table I). Sok RNA bound with similar high rates to truncated wild-type and super-tac hok mRNAs.…”
Section: Resultsmentioning
confidence: 99%